Representasi Kepemimpinan Keluarga oleh Tokoh Moko dalam Film Satu Kakak Tujuh Ponakan - Humaira, Faizza; Amaliyah, Amaliyah; Dimisyqiyani, Erindah; Amalia, Rizky (Journal of Educational Research and Humaniora (JERH), 2025)
Leadership research is not only relevant within organizational contexts but also important to study within the family environment. The film 1 Kakak 7 Ponakan presents an interesting family leadership dynamic that can be analyzed, particularly through the role of Moko as a parental figure substitute. The purpose of this study is to explore how family leadership is represented by Moko and to examine its relevance to the transformational leadership approach. The method used is descriptive qualitative with a narrative approach, conducted through direct observation of key scenes depicting interactions between Moko and his seven nieces and nephews. The findings reveal that Moko prioritizes the family's interests above his own, even sacrificing his personal ambitions for the future of his nieces and nephews. He is also able to motivate, set an example, and foster a sense of togetherness through strong emotional bonds. Moko’s leadership reflects transformational aspects such as sacrifice, shared vision, and the development of collective awareness within the family. These findings contribute significantly to leadership studies by demonstrating that transformational leadership values are not only relevant in organizations but can also be applied in everyday family life.